Embedding more security in digital signature system by using combination of public key cryptography and secret sharing scheme - Sharma, Surbhi (International Journal of Computer Sciences and Engineering, 2025)
The digital signature system is more powerful than the authentication systems, because the digital signatures support both authentication and non-repudiation. Non-repudiation is necessary for the applications like electronic commerce, digital cash, banking applications, electronic voting etc. Here an efficient scheme based on RSA and arbitrary – precision numbers is discussed which is very secure. Also a secret sharing scheme is discussed which is based on visual cryptography. If the private key of users are compromised then intruder can use it illegitimately for signing purpose. So here the ways has been proposed to increase security of digital signatures by using combination of public key cryptography and secret sharing technique.